IDENTIFIKASI KARAKTER VEGETATIF BEBERAPA GENOTIPE PADI LOKAL KABUPATEN KUANTAN SINGINGI - Ezward, Chairil; Indra Dwipa, Irfan Suliansyah, Nalwida Rozen, (Menara Ilmu, 2020)
Characterization is an observation process with the aim to find out the character of a plant. This study aims to identify and characterize 26 local rice genotypes in Kuantan Singingi Regency in the growth phase. This study uses a deliberate sampling method (purposive random sampling). Data was collected by identifying the characteristics of 26 local rice genotypes in Kuantan Singingi Regency directly to the field. Location data collection which is used as a place for sampling is done through exploration. Data observations were made on samples based on the Ministry of Agriculture's (2013) and IRRI's (2007) rice characterization and evaluation system guidelines. The observed characters are qualitative and quantitative characters. Qualitative characters are characters that cannot be measured in units but can be converted through scoring data. Quantitative characters are characters that can be measured by the instrument and have units. Observations on quantitative data are : Plant length, stem diameter, leaf blade length, leaf blade width, ligula length, number of tillers. While the qualitative data are: Auricle color / auricle (WA). Ligule shape / leaf tongue (BL). Color Ligule / leaf tongue (WL). Color Collar / leaf collar (WCo). Plant Shape (BT). Observation data is processed using software Ms. Excel and (NTSYS-pc) version 2.02. Obtained a diversity of morphological characters in the vegetative phase, both quantitative and qualitative. Similarity analysis of 26 local rice genotypes with a 30% similarity coefficient resulted in six (6) groups. Keywords : Characterization, morphology, rice